Writing and Renunciation in Medieval Japan The Works of the Poet-Priest Kamo no Chomei - Pandey, Rajyashree (Michigan Monograph Series in Japanese Studies, 2020)
This is the first monograph-length study in English of Kamo no Chōmei, one of the most important literary figures of medieval Japan. Drawing upon a wide range of writings in a variety of genres from the Heian and Kamakura periods, Pandey focuses on the terms kyōgen kigo (wild words and fancy phrases), shoji soku nehan (samsara is nirvana), hōben (expedient means), and suki (single-minded devotion to an art). She shows how these terms deployed by writers in an attempt to reconcile literary and artistic activities with a commitment to Buddhism. By locating Chōmei within this broad context, the book offers an original reading of his texts, while at the same time casting a light upon intellectual preoccupations that were central to the times. Writing and Renunciation in Medieval Japan is an important contribution to a growing body of work that challenges the rigid distinction between the religious and literary-a distinction that would have made little sense to medieval writers, many of whom were poets as well as priests-and sheds light on the particular ways in which a religio-aesthetic tradition came to be articulated in medieval Japan. Through an examination of records left by Chōmei's contemporaries, the book also traces the life of Chōmei, particularly his activities as a court poet and the circumstances that led to his taking the tonsure. Rajyashree Pandey is Professor of Japanese Studies in the Department of Politics and International Relations at Goldsmiths. She has published widely in the areas of medieval Japanese literature, Buddhism, gender, postcolonial studies and popular culture. Her latest monograph, published by University of Hawaii Press, is Perfumed Sleeves and Tangled Hair: Body, Woman, and Desire in Medieval Japanese Narratives (2016).